THE COMPARISON OF HELMINTH INFECTIONS IN PET SNAKES AMONG AMATEUR AND PROFESSIONAL SNAKE KEEPERS - Jarulė, Virginija; Radziulis, Kęstutis; Urbanavičius, Marius (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The aim of this article is to find out the prevalence of snake helminthiasis among private amateur keepers and professional snake keepers. Untreated animals are vectors of infection, and when ingested, helminths damage the digestive system, weaken the immune system, impair the absorption of nutrients, and the toxins they release, poison the body. As there is still a lack of readily available information on the breeding and care of exotic animals, one of the most common diseases of pet snakes is compared – helminthiasis among professional and amateur snake keepers. Keywords: pet snakes, helminthic infections, coprological analysis, sedimentation method